Analisis Penerapan PSAK 109 pada Laporan Keuangan di BAZNAS Kota Padang - Nanda Amalia Rizki (Jurnal Kajian Islam dan Sosial Keagamaan, 2023)
Zakat is one of the third pillars of Islam, which requires every Muslim who is able and meets the requirements to fulfill it. According to the statement of financial accounting standards PSAK No. 109, zakat is property that must be issued by muzakki in accordance with sharia provisions to be given to those who are entitled to receive it (mustahiq), while infaq / alms are assets that are voluntarily given by their owners, whether the designation is limited (specified) or not limited. This study aims to determine whether Baznas Padang City has implemented PSAK 109 in its financial reporting. This research was conducted at BAZNAS Padang City which is located at Jalan Bypass KM 12, Sungai Sapih Village, Kuranji District, Padang City. This research was carried out using a qualitative method where the data was obtained through financial reports and interviews with parties involved in the financial reports of Baznas Padang City. The results of this study indicate that the financial statements of Baznas Kota Padang are in accordance with PSAK 109. This can be seen in the financial statements which consist of reports on financial position, reports on cash flows, reports on changes in funds, and reports on changes in assets under management.